THE EFFECTS OF FACEBOOK UTILIZATION ON WRITING ACHIEVEMENT AND INTRINSIC MOTIVATION OF MUHAMMADIYAH UNIVERSITY’S UNDERGRADUATE STUDENTS - Asni, Asni (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Facebook is one of the instances of web 2.0. It provides the opportunity to the user of that social media to develop writing skills by means of synchronous and asynchronous communication tools. The objectives of this study are three-fold: (1) to examine the effect of giving feedback through Facebook group on students’ writing achievement. (2) to scrutinize possible changes in students’ intrinsic motivation as a result of using facebook, and (3) to gauge students’ perceptions of using Facebook group in writing class. This study was conducted in Muhammadiyah University involving 120 students of English Study Program registered in academic years of 2014/2015. Purposive sampling technique was employed in recruiting the participants. This study was conducted using mixed method. Quantitave data originated from test scores & questionnaires. Qualitative data are obtained from in-depth interviews with sample participants. The researcher used thematic analysis in analyzing the results of the interview. In-depth interviews with sample students indicate that Facebook is perceived to be effective in improving their writing skills. Paired samples t-test shows that post-test scores are significantly higher than pre-test scores, -4.637 (31) 0.000 < 0.05 which in turn suggests that use of Facebook has resulted in improved writing skills. By the same token, students’ intrinsic motivation too undergoes a significant increase, -2.250 (31) 0.032 < 0.05.